Dropout from Treatment and Desistance from Crime among Released Prisoners in Jerusalem Halfway House for Prisoners with Substance Misuse Disorder - Shoham, Efrat (International journal of offender therapy and comparative criminology, 2022)
The study aims to investigate the rates of recidivism among prisoners on parole with a substance misuse disorder who participated in the Jerusalem halfway-house, which combines supervision, employment, and a comprehensive therapeutic program. The study population included all participants who have been treated in the halfway-house (N = 125), whereas the comparison group included all prisoners with a substance misuse disorder who were released after serving their full sentences (N = 321). To reduce possible selection biases, the Propensity Score Matching method was used. Findings show that prisoners, who were treated at the Jerusalem halfway-house, are characterized by higher and frequent rates of recidivism. However, when only completers of the halfway-house were evaluated, it was found that they had lower and slower rates of recidivism. Findings suggest that completing treatment contributes to desistance from crime in the critical post-release years among participants and indicates the importance of optimal diagnostic processes before admitting prisoners to a halfway-house.